Application of Sustainability Criteria in Identifying Sites for Social Housing in Serbia - Tanja Njegić; Sanja Simonović Alfirević; Tijana Crnčević; Katarina Majhenšek (Land)
An adequate and sustainable site is of crucial importance for the success of a social housing project, because it directly affects the ability to meet the specific housing needs of the target tenants and their social integration into the local community. Applying sustainability criteria in the urban planning of the residual type of social housing in Serbia could prevent additional social exclusion of disadvantaged users, and enable the creation of viable instead of deprived neighborhoods. The aim of this study was to formulate sustainability criteria in identifying sites for social housing, and to evaluate the existing Serbian practice based on a defined multi-criteria model. The key research methods included the identification, systematization, and interpretation of relevant general and specific criteria through a literature review, and a case study in which multi-criteria analysis and a resident satisfaction survey were used. The findings highlight the uneven application of sustainability criteria in past practices and emphasize the need for a more comprehensive and consistent approach. The proposed set of criteria and experience-based guidelines provide a contribution to the still-evolving methodology for the urban planning of social housing in Serbia, which could be adapted to related housing systems in the early stages of development.